2015
DOI: 10.1038/srep15799
|View full text |Cite
|
Sign up to set email alerts
|

UV-Enhanced Sacrificial Layer Stabilised Graphene Oxide Hollow Fibre Membranes for Nanofiltration

Abstract: Graphene oxide (GO) membranes have demonstrated great potential in gas separation and liquid filtration. For upscale applications, GO membranes in a hollow fibre geometry are of particular interest due to the high-efficiency and easy-assembly features at module level. However, GO membranes were found unstable in dry state on ceramic hollow fibre substrates, mainly due to the drying-related shrinkage, which has limited the applications and post-treatments of GO membranes. We demonstrate here that GO hollow fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 31 publications
2
24
0
1
Order By: Relevance
“…However, it is still unclear to what extent the microstructure will affect the permeation flux, and this has prevented us from understanding the transport in GO laminar structures. Chong et al showed that a pristine, well-laminated GO membrane could be turned into a more disordered structure by UV irradiation, and the water permeation was improved from 0.074 to 2.75 LMH bar −1 [23]. The finding demonstrates a critical role of the microstructure when understanding the transport mechanism in GO membranes.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, it is still unclear to what extent the microstructure will affect the permeation flux, and this has prevented us from understanding the transport in GO laminar structures. Chong et al showed that a pristine, well-laminated GO membrane could be turned into a more disordered structure by UV irradiation, and the water permeation was improved from 0.074 to 2.75 LMH bar −1 [23]. The finding demonstrates a critical role of the microstructure when understanding the transport mechanism in GO membranes.…”
Section: Introductionmentioning
confidence: 90%
“…GO suspension was synthesized using a modified Hummer‫׳‬s method, as described in our previous study [17,23]. The GO suspension was centrifuged to control the size of GO flakes, which was determined to be 5 -10 µm from SEM.…”
Section: Preparation Of Go Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, GO membrane were easily shrunk during the drying process and then huge tensile stresses were produced in the membrane which causing obvious defects. More recently, an effective way to solve the stability problem by using the sacrificial layer in the process of membrane preparation was tried by Li et al When the sacrificial layer was washed out, the gap between the GO layers and substrate allowed the GO membrane to shrink freely without pressure [18]. …”
Section: Assembled Graphene Laminatesmentioning
confidence: 99%
“…The unique two-dimensional (2D) structure and the good stability in organic solvents endow graphene nanomaterials to be an ideal candidate for creating novel membranes [15,[21][22][23]. As a result of the uniform interlayer spacing, graphene membranes usually show superior solvents flux and precise molecular sieving for small organic reagents [8,17,18]. Herein, the methods of preparation of different kinds of SRNF membranes with graphene-based nanomaterials are introduced and the comparation of corresponding parameters of different graphene-based SRNF membranes during the filtration process are provided.…”
Section: Introductionmentioning
confidence: 99%